2022
DOI: 10.1038/s41598-022-25901-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between running performance and weather in elite marathoners competing in the New York City Marathon

Abstract: It is well known that weather and pacing have an influence on elite marathon performance. However, there is limited knowledge about the effect of weather on running speed in elite marathoners. The aim of the present cross-sectional study was to investigate potential associations between running speed and weather variables in elite runners competing in the ‘New York City Marathon’ between 1999 and 2019. Data from all official female and male finishers with name, sex, age, calendar year, split times at 5 km, 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…As the enthusiasm for these events continues to grow (Burfoot, 2007;Knechtle et al, 2018;Vitti et al, 2020)], the range of participants has expanded, accommodating both amateur and elite runners, and the performance of participants has steadily improved (Gómez-Molina et al, 2017). Marathon events are influenced by various uncontrollable factors for runners, such as climate conditions including temperature, humidity, and atmospheric pressure, which exhibit seasonal characteristics (Weiss et al, 2022a;Weiss et al, 2022b). Individual characteristics such as age, gender, physical fitness, psychological traits, and conditions, as well as training variables including tactics and pacing strategies, also play a significant role (Boullosa et al, 2020;Cuk et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As the enthusiasm for these events continues to grow (Burfoot, 2007;Knechtle et al, 2018;Vitti et al, 2020)], the range of participants has expanded, accommodating both amateur and elite runners, and the performance of participants has steadily improved (Gómez-Molina et al, 2017). Marathon events are influenced by various uncontrollable factors for runners, such as climate conditions including temperature, humidity, and atmospheric pressure, which exhibit seasonal characteristics (Weiss et al, 2022a;Weiss et al, 2022b). Individual characteristics such as age, gender, physical fitness, psychological traits, and conditions, as well as training variables including tactics and pacing strategies, also play a significant role (Boullosa et al, 2020;Cuk et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in footwear technology aimed at enhancing the running economy have also garnered significant attention in recent years (Muniz-Pardos et al, 2021). Investigations into the impact of weather conditions have revealed that elite runners accelerate as humidity and daylight hours increase (Weiss et al, 2022). The factors influencing marathon performance are intricate and multifaceted, underscoring the criticality of staying abreast of the latest information for the scientific training of marathon runners.…”
Section: Introductionmentioning
confidence: 99%
“…Although long-distance performances, as in the marathon, can be influenced by factors beyond the athlete’s control (e. g. , climate conditions, seasonal characteristics like temperature, humidity and barometric pressure, etc.) 7 8 , they mainly depend on personal characteristics (age, sex, physical qualities, psychological traits and states, etc.) and training variables (tactics, pacing strategy, etc.)…”
Section: Introductionmentioning
confidence: 99%